Hubungan persekitaran sekolah dan guru dengan amalan akhlak murid sekolah menengah Malaysia - Ab Halim Tamuri,; Ahmad Munawar Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2021)
This article examines the moral practice of secondary school students in Malaysia and their perception towards the school environment and the teachers of Islamic education. This article is part of the findings of a study that has used the survey as a method of data collection. The questionnaires were distributed to the students in the form four and lower six of secondary schools in Malaysia. They were selected based on the of multi stages cluster sampling. A total of 3 ,262 students were involved in answering the questionnaires. SPSS software has been used to analyze the data. It can be concluded that, the Islamic practice of Muslim students in secondary schools is categorized as ‘a high level of religious practice’ and their perception on school environment and Islamic education teachers also is high. This study also shows that there is a significant correlation between the Islamic moral practices of students and their perceptions of the school environment, and between Islamic education teachers.